1998
DOI: 10.1192/pb.22.3.150
|View full text |Cite
|
Sign up to set email alerts
|

‘The Health of the Nation’, suicide and the general hospital doctor

Abstract: Records were obtained of all suicide and open verdicts in York (n=127) between 1990–1994 inclusive. Those with no past or current contact with psychiatric services were identified (n=67). The extent and nature of this group's general (i.e. non-psychiatric) hospital contact in the months prior to death was established. Thirteen per cent (9/67) of these received general hospital input in the month before death with eight out of the nine aged over 65. Five of the 67 suicides showed evidence of depression. General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Cattell & Jolley (1995), for example, reported that within the 12 months preceding suicide, 23% of a series of 100 consecutive elderly suicides had been hospitalised for the investigation and treatment of physical disorders. Elwood & De Silva (1998), in a study of 67 subjects who had made contact with general hospital services but were unknown to psychiatric services, found the elderly to be overrepresented. Out of the nine completed suicides who had received hospital care in the month prior to death, eight were over 65 years old.…”
Section: Physical Illnessmentioning
confidence: 99%
“…Cattell & Jolley (1995), for example, reported that within the 12 months preceding suicide, 23% of a series of 100 consecutive elderly suicides had been hospitalised for the investigation and treatment of physical disorders. Elwood & De Silva (1998), in a study of 67 subjects who had made contact with general hospital services but were unknown to psychiatric services, found the elderly to be overrepresented. Out of the nine completed suicides who had received hospital care in the month prior to death, eight were over 65 years old.…”
Section: Physical Illnessmentioning
confidence: 99%